2016
DOI: 10.1111/anoc.12056
|View full text |Cite
|
Sign up to set email alerts
|

The Globalization of Ayahuasca Shamanism and the Erasure of Indigenous Shamanism

Abstract: Ayahuasca is a hallucinogenic plant mixture used in a ceremonial context throughout western Amazonia, and its use has expanded globally in recent decades. As part of this expansion, ayahuasca has become popular among westerners who travel to the Peruvian Amazon in increasing numbers to experience its reportedly healing and transformative effects. Drawing from ethnographic fieldwork in and around the area of Iquitos, Peru, the epicenter of ayahuasca tourism, this paper focuses on some of the problematic aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 30 publications
0
63
0
10
Order By: Relevance
“…Each year, thousands of ayahuasca tourists travel to Peru, generating significant revenue for retreat centers that administer the brew (Fotiou, ). For example, a 2015 study found that in Iquitos, Peru's largest Amazonian city, 10 of the 40 largest retreats generated over USD 6.5 million annually (Álvarez, ).…”
mentioning
confidence: 99%
“…Each year, thousands of ayahuasca tourists travel to Peru, generating significant revenue for retreat centers that administer the brew (Fotiou, ). For example, a 2015 study found that in Iquitos, Peru's largest Amazonian city, 10 of the 40 largest retreats generated over USD 6.5 million annually (Álvarez, ).…”
mentioning
confidence: 99%
“…The idea that the individual is responsible for their own healing is central—it is often said that “everyone is their own shaman”—although healing by intervention of spirits is often reported as well. This focus on healing has led to the sanitization of Amazonian shamanism from its darker aspects, such as sorcery (Fotiou 2010b, 2016).…”
Section: Alterity and Intercultural Translation In Shamanic Tourismmentioning
confidence: 99%
“…This has resulted in the idealisation of shamanic practices. This contemporary idealisation of shamanism has a connection to European romanticisms and American transcendentalisms and their vocalisations of interest in mysterious and spiritual aspects of living (Fotiou 2016).…”
Section: Ethno-tourismmentioning
confidence: 99%
“…However, this is a western use of the originally north Asian, probably Tungusian, term saman, šaman, or xaman (Mongol: šaman, Turkish: kam, xam) for a different region (for the etymology of the word shaman, see Laufer 1917). It has been noted by various authors that this use is also associated with the problematic stereotyping of a shaman's image, for example, its idealisation and promotion as a universal practice regardless of its cultural and temporal context (on stereotypes, see, for example, Wernitznig 2003;Fotiou 2016). One of the rites said by the Shuar to be an ancient practice is Natemamu.…”
Section: The Shuar and The Natemamu Ritementioning
confidence: 99%